A developmental atlas of male terminalia across twelve species of Drosophila - Urum, Anna; Rice, Gavin; Glassford, William; Yanku, Yifat; Shklyar, Boris; Rebeiz, Mark; Preger-Ben Noon, Ella (Frontiers in Cell and Developmental Biology, 2024)
How complex morphologies evolve is one of the central questions in evolutionary biology. Observing the morphogenetic events that occur during development provides a unique perspective on the origins and diversification of morphological novelty. One can trace the tissue of origin, emergence, and even regression of structures to resolve murky homology relationships between species. Here, we trace the developmental events that shape some of the most diverse organs in the animal kingdom—the male terminalia (genitalia and analia) of Drosophilids. Male genitalia are known for their rapid evolution with closely related species of the Drosophila genus demonstrating vast variation in their reproductive morphology. We used confocal microscopy to monitor terminalia development during metamorphosis in twelve related species of Drosophila. From this comprehensive dataset, we propose a new staging scheme for pupal terminalia development based on shared developmental landmarks, which allows one to align developmental time points between species. We were able to trace the origin of different substructures, find new morphologies and suggest possible homology of certain substructures. Additionally, we demonstrate that posterior lobe is likely originated prior to the split between the Drosophila melanogaster and the Drosophila yakuba clade. Our dataset opens up many new directions of research and provides an entry point for future studies of the Drosophila male terminalia evolution and development.